Power Management System For Water Quality Monitoring System In Aquaculture Application - Malik, Azman Ab (2014)
This project proposes a Power Management System (PMS) for water quality monitoring systems in aquaculture applications. The proposed system requires power supply 12V, 200mAh with five sensors, which are ammonium sensor, temperature sensor, water level sensor, dissolve oxygen sensor and pH sensor. The proposed system use lithium ion battery due to its smaller size, lighter, longer life span and stable output voltage. Nowadays lithium ion battery charger is only available for batteries that are arranged in parallel. Hence it is suitable only for 3 V application. However for 12 V system, the voltage have to step up from 3 V to 12V, and it will cause power losses during the step up process. Therefore a charger in series configuration is studied in this project. Four models are developed and studied which are; 1) batteries are arranged in parallel and solar energy is used to charge the battery. 2) batteries are arranged in series and solar energy is used to charged the battery, 3) solar power and batteries that are arranged in parallel are used to supply power for the system, 4) solar power and batteries that are arranged in series are used to supply power for the system. carried out by using the same load. Results show that the second model improves by 173% of discharging rate compared to model 1. Compared with the model 1 and model 2, the model 3 improves by 193% and 7% respectively for the total discharging rate. For the model 4, the discharging rate is better 406%, 85% and 73% compared to model 1, model 2 and model 3 respectively. Results also shows that by using LM2577 as a charger in model 2 and model 4 it xviii Experiments to get charging rate and discharging rate to supply power for the system are